Delivery of bone morphogenetic protein-2 and substance P using graphene oxide for bone regeneration - La, Wan-Geun (Dove Medical Press, 2014)
In this study, we demonstrate that graphene oxide (GO) can be used for the delivery of bone morphogenetic protein-2 (BMP-2) and substance P (SP), and that this delivery promotes bone formation on titanium (Ti) implants that are coated with GO. GO coating on Ti substrate enabled a sustained release of BMP-2. BMP-2 delivery using GO-coated Ti exhibited a higher alkaline phosphatase activity in bone-forming cells in vitro compared with bare Ti. SP, which is known to recruit mesenchymal stem cells (MSCs), was co-delivered using Ti or GO-coated Ti to further promote bone formation. SP induced the migration of MSCs in vitro. The dual delivery of BMP-2 and SP using GO-coated Ti showed the greatest new bone formation on Ti implanted in the mouse calvaria compared with other groups. This approach may be useful to improve osteointegration of Ti in dental or orthopedic implants.